An operational risk analysis of Iran Buyback contract and its policy implication. (June 2017) - Li, Chengyuan; Jiang, Mingjun; Ge, Haiming; Li, Zhen; Luo, Dongkun
Abstract: Buyback contract has played a key role in utilizing foreign investment on Iran's oil and gas industry from the inception. However, the success of buyback has been rarely proved, and there are very limited studies on theoretical risks without digging into operational analysis. Risks are identified by qualitative analysis, and four novel operational risk scenarios are simulated and evaluated by economic evaluation. It is concluded that the risks embedded in Buyback contract should be duly eliminated in new Iranian petroleum contract. The philosophy of integrated managerial system for reservoir in long term, improved policy structuring and coordination between Iranian ministries, solutions for contractual defects, governance structure for higher efficiency, and specific technical details are recommended. Highlights: This is a systematic review of Iran buyback. New operational risks of Iran buyback are identified. Novel risks are defined by qualitative and quantitative analysis. Specific recommendations regarding contract design and improvement for new Iranian petroleum contract are made.